APPLICATION OF NANOSTRUCTURED THERMAL INSULATION MATERIALS TO IMPROVE THE ENERGY EFFICIENCY OF PIPELINES - Максименко, В. (SWorldJournal, 2026)
Improving the thermal performance of pipeline networks remains one of the fastest and most capital‑efficient levers for reducing energy waste, operating costs, and greenhouse‑gas emissions in district heating, industrial steam, and process pipelines. Alon